Mycobacterium gordonae infection in a free-ranging green turtle (Chelonia mydas), Brazil - Goldberg, Daphne Wrobel; Alcala, Marina Molinas; Nóbrega, Daniela Farias da; Sellera, Fábio Parra; Fonseca, Solange; Neto, José Soares Ferreira; Nogueira, Denise Batista; Heinemann, Marcos Bryan (Frontiers in Marine Science, 2023)
Mycobacteriosis is a well-known disease that has been reported in a variety of reptiles species. However, the occurrence of mycobacteriosis in sea turtles has been rarely documented, and most reports are from captive-reared animals. A juvenile green turtle (Chelonia mydas) was found stranded in March 2020, in Guanabara Bay, one of the most urbanized and polluted coastal areas in Rio de Janeiro, Southeastern Brazil. The turtle was in fair body condition and exhibited multiple cutaneous fibropapillomas, covering almost 60% of its body. Despite continued medical therapy, the animal died 60 days after initial supportive care. Necropsy revealed granulomatous pneumonia, hydropericardium, small granulomas in the myocardium, liver, spleen, thyroid and brain and caseous exudate in the meninges of the brain. The histopathological analysis showed disseminated granulomatous inflammation in various organs examined during necropsy. Intrahistiocytic acid-fast bacteria were observed in the liver, heart, lungs, kidneys, spleen, brain and adrenals. The blood culture collected shortly after the animal was admitted tested positive for Mycobacterium gordonae, after an 8-week incubation period; however, the animal had already died by the time the results were obtained. Postmortem examination confirmed systemic mycobacteriosis, identified as M. gordonae in blood, liver and lung cultures and by PCR amplification of DNA extracts from frozen tissue samples. This is the first report of a disseminated infection caused by M. gordonae in a free-ranging sea turtle. Although the source of this Mycobacterium remains unknown, it could potentially be related to anthropogenic activities (e.g., waste dumping or leakage from landfill sites). Increasing surveillance of Mycobacterium in wild sea turtles is of paramount importance to better understand the role of mycobacterial species as causative agents of infections in marine species.